DSS Menentukan Kelayakan Kenaikan Gaji Karyawan PT. Scientex Indonesi dengan Metode SAW - Fillipo, Ronalto (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
PT. Scientex Indonesia is a company engaged in the textile industry. Having head office in Malaysia, PT. Scientex Indonesia requires a decision support system that can help companies to determine which employees are eligible to having salary increase accurately and quickly based on employee performance appraisals. The method used is Simple Additive Weighting (SAW) method. SAW method is used to determine employee performance appraisal which later results from calculation of SAW method will be used as the best solution, in this case is the employees who are eligible to get a raise